Peranan dan Implementasi Strategi Pengembangan Pariwisata Kabupaten Sumba Barat Daya Nusa Tenggara Timur - Kristina Yuniari Holo; Kasanah Kasanah; Waskito Waskito (Indonesian Journal of Geography Education, 2021)
The Role and Implementation of the Tourism Development Strategy of West Sumba Regency East Nusa Tenggara. Indonesian Journal of Geography Education . Tourism has become one of the main drivers of the global economy with a very fast rate of development. The development of tourism as an industry that prioritizes services and services shows a very promising role for the economic growth of a country. This fact is probably caused by the great interest of the world community who began to view that traveling is a necessity. It is conceivable with such a large world population and if 30% agree to view tourism as a necessity of life, how rich are the countries that make this service sector a source of income. The objectives of this study are (1) to determine the role of the Department of Culture and Tourism in Tourism Development in Southwest Sumba Regency, NTT Province. (2) To find out the implementation of the Tourism Development Strategy carried out by the Culture and Tourism Office of Southwest Sumba Regency, NTT Province. This research is a descriptive qualitative research in the form of written words from people and observed behavior. The data was obtained by conducting interviews with related parties so that the results of the study were obtained. The data analysis used is data condensation (data condensation), presenting data (data display), and drawing conclusions or verification (conclusion drawing and verification). The results showed that the role of the Tourism Office in increasing the number of visitors. The Tourism Office carried out various promotions through online media, events, exhibitions, banners and brochures. Increasing motivation by providing training to the community. The Tourism Office empowers the community around the island by providing direction and socialization in making souvenirs.